Organizing the world's money : the political economy of international monetary relations - Cohen, Benjamin J. (New York : Basic Books, 1977)
This book is about international monetary relations. Specifically, it is about the international monetary order- the framework of rules, regulations, conventions, and norms governing the foreign financial conduct of nations. The focus of the book is on the problem of how to organize the international monetary order.
Includes bibliographical references and index.
usc 03/05/18
Loans
Keywords: International finance